Fat Embolism Syndrome Without Bone Fracture: Is It Possible? - Bajraktari, Mustafa; Naco, Majlinda; Huti, Gentian; Arapi, Blerim; Domi, Rudin (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Fat embolism syndrome is a life challenge syndrome. Early diagnosing and treatment can significantly improve the patient’s prognosis and likelihood of success. This syndrome occurs mainly after long bones fractures or orthopedic surgery up to 95% of diagnosed cases, but in unusual situation can be faced as well. These rare situations include diabetes mellitus, video-assisted thoracoscopies, fatty liver, and fat injection in plastic and cosmetic procedures. The likelihood of this syndrome can be increased if multiplex long bones fractures occur in the same patient simultaneously. This syndrome is usually manifested with respiratory changes (hypoxemia and ARDS), neurological focal symptoms (confusion, headache, aphasia, and hemiplegia), and skin abnormalities (petechias, and rush in conjunctiva and oral mucosa). The clinical scenario begins typically after 24−72 h of injury, and mainly, respiratory changes are the first, followed by neurological abnormalities and finally petechias as the most significant sign. CASE REPORT: In this case, we report a rare case of unexpected fat embolism syndrome after soft-tissue minimal trauma. This is the first case that we faced according to literature, and the aim of reporting this case is to emphasize that fat syndrome embolism can happen perhaps in every trauma patient even in minor soft-tissue trauma in absence of bone fractures. CONCLUSION: We strongly suggest that this case should make the physicians taking in consideration fat embolism syndrome even if bone fracture missed, to early diagnosing and adequately treating the patient, and optimizing his chances to survive.